La cittadinanza tra giustizia e democrazia (Firenze University Press, 2023)
The volume offers a portrait of Sergio Caruso as scholar, philosopher, and intellectual, and reflects on his academic and cultural experience. The plurality of essays collected in the book takes on a fundamental concept very dear to him: citizenship. Caruso, at the peak of his maturity, dedicated pages of great importance to it (which the book proposes and discusses) showing, «how this notion – originally an exclusively juridical concept – has acquired increasing importance in the social sciences and in political theory» as no longer and not only a «static set of rights and duties linked to the belonging of the subject to the political community» but a «bundle of social functions» and an «emerging collective force»: therefore a lever for new demands for ‘democracy’.